2009
DOI: 10.1007/s12010-009-8667-z
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Properties of Highly Purified l-Asparaginase from Withania somnifera L. against Acute Lymphoblastic Leukemia

Abstract: Withania somnifera L. has been traditionally used as a sedative and hypnotic. The present study was carried out for the purification, characterization, and in vitro cytotoxicity of L-asparaginase from W. somnifera L. L-Asparaginase was purified from the fruits of W. somnifera L. up to 95% through chromatography. The purified L-asparaginase was characterized by size exclusion chromatography, polyacrylamide gel electrophoresis (PAGE), and 2D PAGE. The antitumor and growth inhibition effect of the L-asparaginase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 27 publications
0
34
0
Order By: Relevance
“…Moreover, alkaline pH (8.0-10) showed optimum pH for most bacterial L-asparaginases activity [60,61]. It has been reported that most plant L-asparaginases have its maximum activity in alkaline pH, and was determined in pH range of 7.5, 8.0 and 8.5 due to the balance between L-aspartic acid and L-aspartate [11,58]. In general most plants show maximum enzyme activity at or near neutral pH [60].…”
Section: Effect Of Phmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, alkaline pH (8.0-10) showed optimum pH for most bacterial L-asparaginases activity [60,61]. It has been reported that most plant L-asparaginases have its maximum activity in alkaline pH, and was determined in pH range of 7.5, 8.0 and 8.5 due to the balance between L-aspartic acid and L-aspartate [11,58]. In general most plants show maximum enzyme activity at or near neutral pH [60].…”
Section: Effect Of Phmentioning
confidence: 99%
“…L-asparaginase was detected in different plant species used as a source of protein for human food [4,9]. Recently, several investigators search some plant sources for L-asparaginase production to meet the increase continuous need for L-asparaginases [10][11][12][13]. L-asparagine is the most abundant metabolite for the storage and transport of nitrogen that is utilized in protein biosynthesis [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the amino acid sequence of plant L-asparaginase is not similar to bacterial enzyme but it is 66% similar and 23% identical to human glycosylasparaginase 11 . The plant L-asparaginase is less toxic as compared to bacterial L-asparaginase 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Among these, bacteria-produced Lasparaginase is the most extensively explored, due to their cost-effective nature (Theantana et al, 2009). Many of the commercially-produce L-asparaginase is derived from Escherichia coli, Erwinia carotovora and Serratia marcescens (Oza et al, 2010). L-asparaginase from these prokaryotic sources was however, discovered to cause allergic reactions and anaphylaxis.…”
Section: Introductionmentioning
confidence: 99%